WNT3A rs752107(C > T) Polymorphism Is Associated With an Increased Risk of Essential Hypertension and Related Cardiovascular Diseases - Ren, Huan; Luo, Jian-Quan; Ouyang, Fan; Cheng, Li; Chen, Xiao-Ping; Zhou, Hong-Hao; Huang, Wei-Hua; Zhang, Wei (Frontiers in Cardiovascular Medicine, 2021)
Essential Hypertension (EH) results in the burden of cardiovascular disease (CVD) such as Heart Failure (HF) and Ischemic Stroke (IS). A rapidly emerging field involving the role of Wnt/β-catenin signaling pathway in cardiovascular development and dysfunction has recently drawn extensive attention. In the present study, we conducted a genetic association between genomic variants in Wnt/β-catenin signaling pathway and EH, HF, IS. A total of 95 SNPs in 12 Wnt signaling genes (WNT3A, WNT3, WNT4, DKK1, DKK2, LRP5, LRP6, CTNNB1, APC, FZD1, FRZB, SFRP1) were genotyped in 1,860 participants (440 patients with EH, 535 patients with HF, 421 patients with IS and 464 normal control subjects) using Sequenom MassArray technology. WNT3A rs752107(C > T) was strongly associated with an increased risk of EH, HF and IS. Compared with WNT3A rs752107 CC genotype, the CT genotype carriers had a 48% increased risk of EH (OR = 1.48, 95% CI = 1.12–1.96, P = 0.006), the TT genotype conferred a 139% increased risk of EH (OR = 2.39, 95% CI = 1.32–4.34, P = 0.003). Regarding HF and IS, the risk of HF in the T allele carriers (CT + TT) was nearly increased by 58% (OR = 1.58, 95% CI = 1.22–2.04, P = 4.40 × 10−4) and the risk of IS was increased by 37% (OR = 1.37, 95% CI = 1.04–1.79, P = 0.025). Expression quantitative trait loci (eQTL) analysis indicated that rs752107 C allele corresponded to a significant reduction of WNT3A expression. We described a genetic variant of WNT3A rs752107 in Wnt/β-catenin signaling strongly associated with the risk of EH, HF and IS for the first time.